Interpersonal Communication by Tour Guides in Psychosocial Trauma Healing Services for Child Victims of Landslide Disaster in West Bandung Regency - Salman Alfarisyi Lesmana; Tresna Wiwitan; Atie Rachmiatie; Rini Rinawati; O Hasbiansyah (Jogjakarta Communication Conference (JCC), 2026)
Cisarua District landslide caused trauma to the victims. Trauma recovery is a crucial stage in the long process of psychological recovery after a disaster. Post-disaster psychological support is essential to reduce the level of trauma in the community, especially for children. One program implemented by the local government is to provide tourism experiences to tourist destinations. The purpose of this study is to examine and analyze the interpersonal communication of tour guides in the context of psychosocial trauma healing for child landslide victims in Cisarua District, West Bandung Regency in 2026. In this study, the researcher used interpersonal communication theory with the concept of interpersonal communication according to Joseph A. DeVito. This study uses a constructivist paradigm, a qualitative method with a Cresswell case study approach and was conducted at an educational tourism destination selected by the West Bandung Regency Government as a destination for the psychosocial trauma healing program. The research subjects were five people, selected purposively because they were considered capable of providing accurate and relevant information. The data used were qualitative and came from two sources, namely primary and secondary data. The data collection method was carried out through literature studies, interviews, observation, and documentation. The study results show that tour guides apply elements of openness, positivity, support, equality, and empathy in their interpersonal communication to promote trauma healing for children after a disaster. In addition to verbal communication, they also use nonverbal communication through body language and expressions, as well as clothing and decorations at tourist destinations. Trauma healing communication can be delivered by non-medical personnel using an interpersonal communication approach. Tour guides can integrate interpersonal communication techniques into psychosocial trauma healing services for children after a disaster.